The Impact of Social Concepts on Adventure Tourism Participation: A Mixed Method Study - Pranoto, Pranoto; Sukrisno, Sukrisno; Supriyanto, Sapto; Listyorini, Haniek; Soehari, Hartoyo; Kundori, Kundori (Research Center and Case Clearing House PPM School of Management, 2024)
Self-identity theory in social psychology highlights the importance of social groups, interactions, and context in shaping an individual's sense of self and how this self-identity influences thoughts, feelings, and behavior. This research seeks to review various literature on adventure tourism by providing a specific exploration of the role of self-identity in triggering participation in forms of adventure tourism using a mixed-method research design, 50 visitors were identified as informants for the qualitative research, and 329 respondents were surveyed as visitors to surfing tourist destinations at Menganti, Widarapayung, and Parangtritis beaches. All hypotheses proposed in this research were accepted. This shows that comparisons between regions show little difference among young consumers. The model presented and tested in this research provides a solid theoretical framework and can help understand self-identity as a driver of consumer participation. Managerial implications can provide understanding for surf destination managers so that they reflect the importance of creating a positive attitude towards the product before traveling.